ANALISIS PENGARUH LOCAL STRONGMAN PADA PEMILIHAN BUPATI DAN WAKIL BUPATI DI KABUPATEN INDRAGIRI HULU TAHUN 2020 - Sundari, Dicky; Handoko, Tito (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The local strongman phenomenon is actually contrary to Law of the Republic of Indonesia Number 1 of 2015 concerning the Stipulation of Government Regulations in Lieu of Law Number 1 of 2014 concerning the Election of Governors, Regents and Mayors into Law and Law of the Republic of Indonesia Number 8 of 2015 concerning Amendments to Law Number 1 - 2015 concerning the Stipulation of Government Regulations in Lieu of Law Number 1 of 2014 concerning the Election of Governors, Regents and Mayors into Law. This research aims to determine the influence of local strongmen on the election of Regent and Deputy Regent in Indragiri Hulu Regency in 2020. This research was conducted qualitatively with a descriptive approach, involving observation and interviews with resource persons who have been determined to answer the problem formulation in this research. . The results of this research reveal that the local strongman phenomenon is clearly visible in Indragiri Hulu Regency, where Yopi Arianto's family and the Riau Golkar Party that he raised there are a real reflection of the work of local strongmen in Indragiri Hulu Regency. Golkar gave a recommendation to Rezyta Meylani, wife of the Regent of Indragiri Hulu (Inhu) Yopi Arianto, to run for the 2020 regional elections. This determination is said to have gone through an internal mechanism at Golkar. Then, we can review the facts on the ground that Rezita Meylani has a coordination network in each village, this of course cannot be separated from the role of Yopi Arianto as the previous regent who is the husband of Rezita Meylani, the current regent of Indragiri Hulu. Keywords: local strongman, political patronage, regent of Indragiri Hulu